Morphological Stylistic Analysis in William Blake’s Poem “Spring” - Nasution, Atikah Auni; Matanari, Desna Uli; Fianda, Afiqah; Sasmita, Rheina; Rangkuti, Rahmadsyah (Universitas Negeri Padang, 2024)
Morphemes used in the poem can alter the reader's perception and interpretation of the poem's meaning and message. It demonstrates the variety of language and the freedom of expression enabled by using morphemes in literature, particularly poems. This study aims to identify several types of free and bound morphemes, such as lexical, functional, derivational, and inflectional morphemes found in William Blake's Poem